Study of Commitment to The Organization Based on Intrinsic and Extrinsic Job Satisfaction on Private Campus - Wasi Bagasworo, SE., MM. (Indonesia Banking School, 2017)
Competition in education industry especially college is very tight. It is experienced by STIE XYZ which does not reach the target of new student admission in 2015 and 2016. Unachieved student targets are added to the level of student discharge at the 2nd level of 10-15% of the total students of the first batch. One of the causes of the decline and discharge rate of students is possible because of student dissatisfaction. The organizational commitment questionnaire (OCQ) designed by Allen & Mayer (1990) is enhanced by Ikwukananne I. Udechukwu (2006) used as a measurement tool for affective commitment, continuance commitment, and normative commitment. This study is descriptive by using questionnaire respondents as much as the population of 39 permanent employees of STIE XYZ in 2015. The data were processed using SPSS 21 for instrument test, classical assumption test and hypothesis test with t-test. The results show that commitment to the organization is positively influenced by inner job satisfaction and is not influenced by extrinsic job satisfaction. Inintrinsic job satisfaction that needs to be considered is the issue of security/stability and job authority. Some suggestions that can be done is to provide a clear job description and standard operating procedures when employees occupy job positions, career paths for employees, job rotation based on employee competence and the need for information disclosure according to procedures and authority.